Competencies of Successful Entrepreneurs: Perspectives of Students and Entrepreneurs - Denmoree, Pornpasit; Sathirakul Tachaphahapong, Sirichan; Chandrachai, Achara (Journal of Business, Innovation and Sustainability (JBIS), 2023)
The objectives of this research were 1) To study the entrepreneurial competencies of entrepreneurs in manufacturing, trading and service businesses 2) to study the competencies of students and 3) to compare the competency between entrepreneurs and students by opinion level. The sample groups used for the research were 1) 390 undergraduate students, quota sampled by university categories; and, 2) 20 purposively sampled entrepreneurs. The tools used in this survey research were interviews and questionnaires. Data were analyzed by descriptive statistics using percentage, mean and standard deviation, and t-test. The research conclusions are as follows. 1) Entrepreneurs have a high level of opinion on entrepreneurial competencies (x̄ = 3.92). 2) Students have a medium level opinion on entrepreneurial competencies (x̄ = 3.39). 3) In comparing entrepreneurs and students in terms of their entrepreneurial competencies, there is a significance level of 0.05 in all three aspects, the average entrepreneurs’ opinion level being higher than that of students.